Mengimplementasikan Hasil Pemetaan Sosial untuk Meningkatkan Sektor Sosial Ekonomi di Desa Tumbang Olong II - Yorgen Kaharap,; Ida Bagus Suryanatha, (Joong-Ki : Jurnal Pengabdian Masyarakat, 2024)
Tumbang Olong II Village is located in Palangka Raya Regency. The definition of socioeconomic mapping includes the identification, analysis, and mapping of the distribution of various social and economic variables within a geographical area. The implementation of this activity is carried out through several stages, namely: Observation of local issues, opportunities and potentials of Tumbang Olong II Village. This program aims to increase the attractiveness of village tourism and create new business opportunities for the community. These community empowerment programs are designed to answer the needs and aspirations of the people of Tumbang Olong II Village. With good and sustainable implementation, these programs are expected to improve village welfare, health, education, and infrastructure, as well as create an independent and prosperous community. Community empowerment based on local potential is not only an effort to improve economic welfare, but also a strategy to strengthen the identity and independence of village communities in the long term.